Editorial: Realizing livelihood and environmental benefits of forages in tropical crop-tree-livestock systems - Chirinda, Ngonidzashe; Peters, Michael; Burkart, Stefan; Notenbaert, An Maria Omer; Hoek, Rein van der (Frontiers Media, 2022)
The papers in this collection, which explored livestock production systems in Latin America, Africa and Asia, all suggest the possibility of increasing livestock productivity by adopting innovative policies, technologies, and management practices. The presented evidence suggests that the inclusion of legumes in grazed pastures has the potential to increase cattle production (Valencia et al., 2021), reduce methane emissions (Quintero-Anzueta et al., 2021) and increase the persistence of forage grasses (Valencia et al., 2021). Including feed supplements such as Altoandina oat silage was reported to be an economically viable option for increasing the productivity of Colombia's High-Altitude Dairy Systems (Enciso et al., 2021). Management options that optimize rotational pasture grazing based on simple metrics such as sward height may increase livestock productivity and reduce enteric methane emissions grazing cattle (Marín Gómez et al., 2021). Besides the adoption of better pasture management systems, genetic innovations can be used to overcome challenges such as droughts (Carvajal-Tapia et al., 2021), soil salinity (Liu et al., 2022 and low biomass accumulation (Mwendia et al., 2021).An additional emerging use of tropical forages is their potential as a food source for edible insects (Bawa et al., 2020;Oonincx et al., 2020). Buitrago et al. (2021) share their perspectives on this aspect and suggest that integrating tropical forage-based diets in edible insect production systems represents low-cost feed sources for insects and supports transiting to circular economies. On the other hand, as Hernández et al.(2021) highlight, tropical forage production systems must be protected from harmful insects such as Spittlebugs. Narjes Sanchez et al. ( 2021) also provide critical insights into the possible role of tropical forage legumes in pollinator conservation efforts, income generation, and closing the forage legume seed bottleneck that still limits further advances in sustainable intensification efforts of the cattle sector as of today.In addition to providing food, the livestock sector can generate ecosystem benefits such as increased onfarm agro-biodiversity, soil restoration, mitigation of GHG emissions and more efficient use of nutrients and water resources. Sanchez et al. (2021) showed that silvopastoral systems have the potential to support the provision of ecosystem services such as pollination. In a separate study, Notenbaert et al. (2021) used previous studies to demonstrate the multiple potential benefits of managed livestock production systems. They further demonstrate linkages between managed livestock production systems and agroecology and how the sustainable intensification of livestock production systems can contribute to the 13 principles of agroecology.From this paper collection, it appears there is clarity on what needs to be done to sustainably intensify tropical livestock production systems to meet livelihood, food security and environmental goals. Nevertheless, the slow progress appears disproportionately attributable to non-technical aspects such as a disconnect between institutions and other actors along livestock value chains resulting in insufficient synchrony of efforts to support the adoption of critical innovations (Enciso et al., 2022). While the need to sustainability intensify livestock production systems at the national and global levels is frequently well articulated, connections between policies and investments and, thus, actions on the ground largely remain weak (Lerma et al., 2022). Chirinda et al. (2021) emphasize the need to create inclusive and creatively organized livestock value chains that improve stakeholder linkages, information flows and equity.